Effects of C2-Ceramide and Oltipraz on Hepatocyte Nuclear Factor-1 and Glutathione S-Transferase A1 in Acetaminophen-Mediated Acute Mice Liver Injury - Ma, Xin; Chang, Yicong; Zhang, Yuanyuan; Muhammad, Ishfaq; Shi, Chenxi; Li, Rui; Li, Changwen; Li, Zhi; Lin, Yuexia; Han, Qing; Liu, Fangping (Frontiers in Pharmacology, 2018)
Acute liver injury mice model induced by acetaminophen (APAP) was used to study the effects of C2-ceramide and oltipraz on hepatocyte nuclear factor 1 (HNF-1) and glutathione S-Transferase A1 (GSTA1). Notably, added C2-ceramide to APAP model mice caused alteration in serum transaminases and liver tissue indexes, and aggravated hepatic injury, while oltipraz alleviated hepatic injury. By screening, the optimal concentrations of C2-ceramide and oltipraz were confirmed to be 120 μmol/L and 150 μmol/L, respectively. In histopathology, karyolysis and more necrotic cells and bleeding spots were appeared on administration of C2-ceramide, but only a small amount of inflammatory cells infiltration was seen after oltipraz treatment. In addition, RT-PCR and western blot results revealed that with the administration of 120 μmol/L C2-ceramide to APAP model mice, the mRNA and protein expression levels of HNF-1 and GSTA1 in liver were significantly decreased (p < 0.01), meanwhile, GSTA1 content in serum increased 1.27 fold. In contrast, 150 μmol/L oltipraz incorporation to APAP model mice resulted in obvious elevation (p < 0.01) in the mRNA and protein expression levels of HNF-1 and GSTA1 in liver, meanwhile, serum GSTA1 content decreased unto 0.77 fold. In conclusion, C2-ceramide could down-regulate the expression of HNF-1 and GSTA1 which exacerbated hepatic injury, while oltipraz could up-regulate the expression of HNF-1 and GSTA1 which mitigated hepatic injury.